Development of Chemistry Textbooks Based Scientific Approach in Efforts to Implement Prototype Curriculum at Schools - Riska Imanda; Ayu Rahmi; Sri Setiawaty; Ayu Daun Dandina; Nadia Humaira (Jurnal Penelitian Pendidikan IPA, 2022)
The purpose of research is to develop the chemistry textbook based on the scientific approach in implementing the prototype curriculum in schools. The development of textbooks uses the type of R & D. The R & D model used is ADDIE model which has five Phases, namely (1) analysis, (2) design, (3) development, (4) implementation, and (5) (evaluation). At the analysis is carried out with initial analysis, participant analysis students, task analysis, concept analysis, and formulating learning objectives. At Phase design is carried out preparation of core competency (KI) and basic competencies (KD), preparation of the grid/framework module, and the initial draft of the module. The development includes the assessment Phase of the expert team on the developed textbooks. Implementation and evaluation phase includes development trials to see the effectiveness of the developed textbooks. The research subjects consisted of 9 teachers’ chemical. Data collection is carried out to determine the feasibility of products that have been developed through a validation questionnaire filled out by experts and response questionnaire teachers are also students. The results showed that the -based chemistry textbooks scientific approach developed has received a very feasible assessment by experts to be tested for its use in learning. Next, the teacher's response and students towards scientific approach the developed at the trial Phase is classified as a very feasible category to be implemented in learning. In addition, chemistry textbooks based on a scientific approach are effectively used as a textbook.